Absence without official leave (AWOL) - Ali Mohamed, Ashgar Ali (The Malaysian Current Law Journal Sdn Bhd, 2015)
An employee who absents himself from the workplace on a scheduled workday, will inevitably disrupt the employer’s work schedules, aside from affecting the employer’s customer commitments, amongst other things. To minimise the work disruption due to the slack caused by an absent employee, a regular worker would in normal circumstances assume the added workload. unless and until the annual leave request has been formally and properly approved by the employer, an employee should not absent himself from work. An unauthorised absence from the workplace without any prior approval or permission of the employer is an outright violation of discipline. Hence, in this paper the author argued that a worker who absents himself from work for two or more consecutive days without leave or permission, who exceeds his leave beyond the sanctioned period or who is absent from his place of work without permission, is said to have committed a gross misconduct, and if the allegation is established, the employer is entitled to impose appropriate punishment up to and including dismissal.